Global Trends in YouTube and Google Search Activity for Psoriasis and Atopic Eczema: Detecting Geographic Hot Spots, Blind Spots and Treatment Strategies. Issue 4 (30th June 2020) - Hongler, Valentina N. S.; Navarini, Alexander; Brandt, Oliver; Goldust, Mohamad; Mueller, Simon M.
Abstract: To date, the geographical distribution and global trends of search activities on psoriasis and atopic eczema on Google and YouTube are widely unknown. The aim of this study was to identify geographic and temporal trends in YouTube and Google search activities for psoriasis and atopic eczema. We used specific filter settings on Google Trends to indicate the global search activity for ("Psoriasis") and ("Atopic Eczema") on Google and YouTube between January 1 st, 2008 and August 7 th, 2019. The four resulting data sets were analyzed and compared with respect to geographic distribution and temporal trends. Apart from a few "blind spots" (eg, Chad, Uzbekistan) the term "Psoriasis" was queried geographically fairly evenly distributed. The opposite was true for "Atopic Eczema", which was predominantly queried from a few "hot spots" (eg, United States, Commonwealth of Nations and Sweden). Since 2008, the search activity on YouTube for "Psoriasis" has tripled, while that for "Atopic Eczema" has decreased. On Google, by contrast, search activity has risen for both "Psoriasis" and "Atopic Eczema." Google Trends can be a useful tool to track people's/patients' interests and search search behavior over time, enabling, for instance, regionally tailored information and prevention campaigns.